(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
work There was a study of the clinical and morphological signs of the brain tumor, identification of prognostically significant factors among them, analysis of the results of surgical treatment and the development of rational treatment tactics for these brain tumors.